2003
DOI: 10.1021/ja037308l
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Analysis of Liquid/Liquid Interfaces in Multiphase Microflows

Abstract: Microscopic quasi-elastic laser scattering (muQELS) spectroscopy has been developed for analysis of interfacial phenomena at laminar multiphase microflow in a microchannel. Transport phenomena of a metal chelate through a water/toluene interface were measured, and transient adsorption of the chelate in the initial step of the transport was measured. A water/methanol miscible interface was also measured, and the interfacial free energy of a miscible interface was determined for the first time. The muQELS is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…Therefore, novel MUOs taking these issues into account are needed. Kitamori et al have developed MUOs for various purposes, such as mixing and reaction [4,5], phase confluence and separation [6][7][8][9][10][11][12][13][14][15][16][17], solvent extraction [18], gas/liquid extraction [19][20][21][22], solid-phase extraction and reaction on surfaces [23][24][25][26][27][28][29][30][31][32][33][34], heating [35][36][37][38][39], cell culture [40][41][42][43][44], and ultrasensitive detection [45][46][47][48][49][50][51][52]…”
Section: Design and Fabrication Methodology For Integration Of Complementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, novel MUOs taking these issues into account are needed. Kitamori et al have developed MUOs for various purposes, such as mixing and reaction [4,5], phase confluence and separation [6][7][8][9][10][11][12][13][14][15][16][17], solvent extraction [18], gas/liquid extraction [19][20][21][22], solid-phase extraction and reaction on surfaces [23][24][25][26][27][28][29][30][31][32][33][34], heating [35][36][37][38][39], cell culture [40][41][42][43][44], and ultrasensitive detection [45][46][47][48][49][50][51][52]…”
Section: Design and Fabrication Methodology For Integration Of Complementioning
confidence: 99%
“…Integration of chemical processes utilizing solvent extraction has been demonstrated for various applications [8][9][10][11][12][13][15][16][17]. Here, we focus on two such examples.…”
Section: Analysis Methods Using Solvent Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ interfacial tension measurement remains a significant challenge, although some attractive image-based methods, [132][133][134] a light scattering method, 135,136 and an electrochemical method 137 have been reported. These new challenges are expected to advance the science and technology in this field in the next years.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Kovalchuk et al [21][22][23][24][25][26][27][28][29][30][31][32] showed that the dynamics at an air/water or a water/ organic interface affect the heterogeneity of the interfacial tension caused by the addition of an alcoholic surfactant through a capillary. Using time-resolved quasi-elastic laser scattering (QELS) measurements, [33][34][35][36][37][38][39][40][41][42][43] Ikezoe et al [33][34][35] found that surfactant molecules are rapidly adsorbed and gradually desorbed when an aqueous surfactant solution is introduced to the interface between aqueous and organic phases with a capillary.…”
Section: Introductionmentioning
confidence: 99%